Role of HLA-DP Expression in Graft-Versus-Host Disease After Unrelated Donor Transplantation - Petersdorf, Effie W; Bengtsson, Mats; De Santis, Dianne; Dubois, Valerie; Fleischhauer, Katharina; Gooley, Ted; Horowitz, Mary; Madrigal, J Alejandro; Malkki, Mari; McKallor, Caroline; Morishima, Yasuo; Oudshoorn, Machteld; et al. (Journal of clinical oncology, 2020)
The main aim of this study was to evaluate the significance of HLA-DPB1 expression in acute graft-versus-host disease (GVHD) after hematopoietic cell transplantation (HCT) from HLA-A, -B, -C, -DRB1, -DQB1-matched and -mismatched unrelated donors. Between January 1, 2017, and January 10, 2019, we assessed 19,136 patients who received HCT from an HLA-A, -B, -C, -DRB1, -DQB1-matched or -mismatched unrelated donor performed in Australia, the European Union, Japan, North America, and the United Kingdom between 1988 and 2016. Among transplant recipients with one HLA-DPB1 mismatch, the patient's mismatched HLA-DPB1 allotype was defined as low or high expression. Multivariable regression models were used to assess risks of GVHD associated with high expression relative to low expression HLA-DPB1 mismatches. The effect of increasing numbers of HLA-DPB1 mismatches on clinical outcome was assessed in HLA-mismatched transplant recipients. In HLA-A, -B, -C, -DRB1,-DQB1-matched transplant recipients, donor mismatching against one high-expression patient HLA-DPB1 increased moderate (odds ratio [OR], 1.36; = .001) and severe acute GVHD (OR, 1.32; = .0016) relative to low-expression patient mismatches, regardless of the expression level of the donor's mismatched HLA-DPB1. Among transplant recipients with one HLA-A, -B, -C, -DRB1, or -DQB1 mismatch, the odds of acute GVHD increased with increasing numbers of HLA-DPB1 mismatches (OR, 1.23 for one; OR, 1.40 for two mismatches relative to zero mismatches for moderate GVHD; OR, 1.19 for one; OR, 1.40 for two mismatches relative to zero for severe GVHD), but not with the level of expression of the patient's mismatched HLA-DPB1 allotype. The level of expression of patient HLA-DPB1 mismatches informs the risk of GVHD after HLA-A, -B, -C, -DRB1, -DQB1-matched unrelated HCT, and the total number of HLA-DPB1 mismatches informs the risk of GVHD after HLA-mismatched unrelated HCT. Prospective consideration of HLA-DPB1 may help to lower GVHD risks after transplantation.